Manufacturing Firm Value Drivers through Return on Assets, Return on Equity and Earning per Shares - Gita Fitriningsih; Ery Yanto; Pandu Adi Cakranegara (JAAF (Journal of Applied Accounting and Finance), 2021)
The company's goal is to create value. Therefore, it is important for companies to know the source of the company's value creation. This study connects the independent factors that affect firm value, namely Return On Equity, Return On Assets, and Earning Per Shares. This research used a sample of 30 companies. The samples used in this research are manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2019 with the sampling technique using purposive sampling. The results indicated that the return on assets has no significant effect on share prices, return on equity has no significant effect on share prices, EPS has an significant effect on share prices and simultaneously return on assets, return on equity and earnings per share has an significant effect on share prices.